1979
DOI: 10.1159/000176264
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise on Plasma and Liver Lipids of Rats

Abstract: The effects of treadmill exercise on hepatic cholesterogenesis and fecal steroid excretion were studied using male Wistar rats fed a commercial pellet ration. Exercise, in comparison with ad libitum or pair-feeding sedentary groups, caused the following significant changes: (i) a reduction in the concentration of plasma triglyceride, phospholipid and cholesterol; (ii) a reduction in liver weight; (iii) increases in hepatic 3-hydroxy-3-methylglutaryl-CoA reductase activity and incorporation of mevalonate into d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…LCAT activity showed decreasing values as dietary protein levels decreased and its activity was raised by voluntary exercise in all groups. Keywords voluntary exercise, protein-deficient diet, serum lipoprotein, high density lipoprotein, lecithin: cholesterol acyltransferase (LCAT), serum electrophoretic patterns Many investigations concerning the effects of exercise on serum lipids have been reported from a preventive point of view; for instance, hyperlipemia and atherosclerosis have often been discussed with regard to the relationship between exercise and health (1)(2)(3)(4). Furthermore, the relation between physical exercise and serum lipoprotein or lecithin: cholesterol acyltransferase has also been reported by Lopez-S et al (S).…”
Section: Discussionmentioning
confidence: 99%
“…LCAT activity showed decreasing values as dietary protein levels decreased and its activity was raised by voluntary exercise in all groups. Keywords voluntary exercise, protein-deficient diet, serum lipoprotein, high density lipoprotein, lecithin: cholesterol acyltransferase (LCAT), serum electrophoretic patterns Many investigations concerning the effects of exercise on serum lipids have been reported from a preventive point of view; for instance, hyperlipemia and atherosclerosis have often been discussed with regard to the relationship between exercise and health (1)(2)(3)(4). Furthermore, the relation between physical exercise and serum lipoprotein or lecithin: cholesterol acyltransferase has also been reported by Lopez-S et al (S).…”
Section: Discussionmentioning
confidence: 99%
“…Many investigations concerning the effects of exercise on serum and liver lipids have been reported from a preventive point of view, for instance hyperlipemia and atherosclerosis, with regard to the relationship between exercise and health (6,7,26,27). MORRIS and HEADY (8) suggested that physical activity in work is associated with a lower incidence of coronary heart disease in middle-aged men.…”
mentioning
confidence: 99%
“…Namely, decreasing the level of dietary protein results in increased plasma and liver cholesterol and liver fat levels (9,30). So far it is known that exercise causes a reduction in the level of plasma lipids (6,7). But there are few reports concerned with the effect of a combination of exercise and dietary protein levels on plasma and liver lipids.…”
mentioning
confidence: 99%
“…Previously, it has been found that the body weight gains of rats are decreased by training (5,6). In the present study, the 20% E group had smaller body weight gains than the nonexercise group.…”
Section: Discussionmentioning
confidence: 99%